2019
DOI: 10.1109/jproc.2018.2869760
|View full text |Cite
|
Sign up to set email alerts
|

Logic Synthesis for Established and Emerging Computing

Abstract: | Logic synthesis is an enabling technology to realize integrated computing systems, and it entails solving computationally intractable problems through a plurality of heuristic techniques. A recent push toward further formalization of synthesis problems has shown to be very useful toward both attempting to solve some logic problems exactly-which is computationally possible for instances of limited size todayas well as creating new and more powerful heuristics based on problem decomposition. Moreover, technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 109 publications
(150 reference statements)
0
16
0
Order By: Relevance
“…In [24], the authors present Majority-Inverter Graph (MIG), a new logic manipulation structure consisting of threeinput majority nodes and regular/inverted edges. Logic functions are represented by MIGs and further optimized using both algebraic and Boolean methods, summarized in [23], [24]. A selection of circuits from both IWLS'05 benchmarks and HDL arithmetic benchmarks were considered and synthesis results obtained with MIG optimization tool were compared to And-Inverter Graphs (AIG) optimized by ABC in terms of logical levels.…”
Section: Carry = Ab+bc In +Ac Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In [24], the authors present Majority-Inverter Graph (MIG), a new logic manipulation structure consisting of threeinput majority nodes and regular/inverted edges. Logic functions are represented by MIGs and further optimized using both algebraic and Boolean methods, summarized in [23], [24]. A selection of circuits from both IWLS'05 benchmarks and HDL arithmetic benchmarks were considered and synthesis results obtained with MIG optimization tool were compared to And-Inverter Graphs (AIG) optimized by ABC in terms of logical levels.…”
Section: Carry = Ab+bc In +Ac Inmentioning
confidence: 99%
“…Hence, a majority gate is a democratic gate and can be expressed in terms of Boolean AND/OR as M AJ(a, b, c) = a • b + b • c + a • c, where a, b, c are Boolean variables. Although majority logic was known since 1960, there has been a revival in using it for computation in many emerging nanotechnologies (spin waves, magnetic Quantum-Dot cellular automata, nano magnetic logic, Single Electron Tunneling [21]- [23]). Recent research [22]- [25] has confirmed that majority logic is to be preferred not only because a particular nanotechnology can realize it, but also because of its ability to implement arithmetic-intensive circuits with less gates.…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the driving questions in logic synthesis, which is the process of optimizing logic representations under various criteria. Decades of research on this have considered various circuit models and produced many synthesis algorithms [1], [2], [3], [4]. In general, the problem of finding the smallest circuit for a given Boolean function is a computationally difficult task, and exact minimization is reasonably fast only for Boolean functions with a small number of inputs.…”
Section: Introductionmentioning
confidence: 99%
“…This notion of equivalence is called NPN (Negation-Permutation-Negation) equivalence [10], [11]. Formally, two Boolean functions are NPN equivalent if one can be obtained 1 Unlike the 3-input majority gate, a general 3-input gate can be asymmetric, thus in such a DAG representation, the ordering of the fan-in must be specified as well. Table I.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond-CMOS research has been underway in the last decade to find an alternative device which is better than CMOS in its characteristics. This includes CMOS-like devices (tunnel FET, GaN TFET, Graphene ribbon pn junction, Ferroelectric FET) [4], quantum-dot cellular automata (QCA), nanomagnet logic, resistance-switching devices (Resistive RAM, Phase Change Memory, conductive bridge RAM), spin-based devices, and plasmonic-based devices [5]. Although some of these post-CMOS devices possessed valuable features like low-voltage operation and non-volatility, recent bench-marking efforts seem to suggest that none of these devices could outperform CMOS in the most critical aspects of computing (energy, latency and area) [4,6].…”
Section: Introductionmentioning
confidence: 99%